Examining Outcome-Based Education (OBE) in Writing Class: Project-Based Assessment Analysis - Yulis Setyowati (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
The call for the implementation of Outcome-Based in Indonesia has been emphasized since 2019, highlighting the necessity for adjustments in the higher education context. In English academic writing classes, incorporating OBE principles presents challenges, particularly in the realm of assessment. The assessment process must effectively evaluate all abilities, skills, and knowledge specified in the learning outcomes. These challenges are further amplified by the large class sizes, resulting in suboptimal assessments of students' writing abilities. Therefore, Project Based assessment that aligns with OBE principles and assists academic writing lecturers in addressing the complexities of providing quality assessments to a multitude of students in Indonesia is of utmost significance. The Proposal Writing Course Universitas Wijaya Putra, consisting of twelve students from the English Department, utilizes the OBE-Project-based assessment method. This study aims to describe the students’ composition as the learning output based on the writing rubrics assessment. The analysis of the student’s proposals revealed a notable enhancement in various aspects, including the context, literature review, research design, and data. It is found that Project Based assessment that aligns with OBE principles significantly enhances their research writing skills and improves their academic achievement throughout the research process. analysis. The incorporation of project-based assessment in OBE in the courses holds great potential for elevating the academic performance of graduate school students engaging in proposal writing courses.